Bivalirudin as compared to unfractionated heparin among patients undergoing coronary angioplasty - De Luca, Giuseppe; Cassetti, Ettore; Verdoia, Monica; Marino, Paolo (Thrombosis and Haemostasis, 2009)
It has been shown that bleeding complications are associated with higher mortality rates among patients undergoing coronary angioplasty. Due to its properties, bivalirudin may provide benefits in terms of bleeding and thrombotic complications as compared to unfractionated heparin (UFH).The aim of the current study was to perform a meta-analysis of randomised trials to evaluate whether bivalirudin might offer benefits in terms of mortality as compared to UFH.We obtained results from all randomised trials evaluating the benefits of adjunctive bivalirudin as compared to UFH with or without Gp IIb-IIIa inhibitors among patients undergoing coronary angioplasty. The literature was scanned by formal searches of electronic databases (MEDLINE and CENTRAL) from January 1990 to October 2008.The following keywords were used: randomised trial, coronary angioplasty, stent, reperfusion, primary angioplasty, bivalirudin, direct thrombin inhibitors, hirulog. Primary endpoint was mortality. Secondary endpoint was infarction. Safety endpoint was the risk of major bleeding complications. No language restriction was applied.A total of nine randomised trials were included in the metaanalysis, with 15655 patients randomised to bivalirudin and 13104 patients randomised to UFH. We did not observe any difference in mortality between bivalirudin and UFH (1.73% vs 1.67%, p = 0.15) without any relationship between the baseline risk of mortality (r = 0.17, p = 0.71) or the reduction in major bleeding complications (r = –0.29, p = 0.53) and the benefits in mortality with bivalirudin. A trend in higher risk of myocardial infarction was observed with bivalirudin (6.9% vs 5.9%, p = 0.07, p het = 0.65). Bivalirudin was associated with a significant reduction in major bleeding complications (1.7% vs 3.4%, p < 0.0001), as compared to UFH.This meta-analysis shows that among patients undergoing coronary angioplasty, bivalirudin is associated with significant reduction in major bleeding complications. However, these benefits did not translate into benefits in mortality, with even a trend in higher risk of myocardial infarction.
Keywords: Antithrombin; clinical trials; direct antithrombin agents; acute myocardial infarction; coronary angioplasty; bivalirudin